2009
DOI: 10.1136/bjo.2008.149591
|View full text |Cite
|
Sign up to set email alerts
|

Sterility control and long-term eye-bank storage of cultured human limbal epithelial cells for transplantation

Abstract: This study is the first to verify the sterility of HLEC cultures prior to transplantation. Although a slight decrease in viability was observed following 2 weeks of storage, the HLEC sheets remain acceptable, whereas 3 week's storage was unsatisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…We previously investigated the effect of 5°C, 23°C and 31°C storage on the viability of cultured human limbal epithelial cells, concluding that 5°C and 31°C storage yielded inferior viability. 19 Storage at 23°C, or ambient temperature, has proven suitable in several studies, 9, 18, 19, 28, 29 including a recent study on the storage of cultured HCjE. 30 Corneal epithelial cells encapsulated in alginate reportedly maintained a higher percentage of viable cells after storage at ambient temperature (18°C–22°C) than when stored at 4°C or 31°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously investigated the effect of 5°C, 23°C and 31°C storage on the viability of cultured human limbal epithelial cells, concluding that 5°C and 31°C storage yielded inferior viability. 19 Storage at 23°C, or ambient temperature, has proven suitable in several studies, 9, 18, 19, 28, 29 including a recent study on the storage of cultured HCjE. 30 Corneal epithelial cells encapsulated in alginate reportedly maintained a higher percentage of viable cells after storage at ambient temperature (18°C–22°C) than when stored at 4°C or 31°C.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the PI viability analysis, the percentage of remaining viable and dead cells following four-day storage at 4°C, 12°C and 24°C was measured using a CAM/EH-1 Live/Dead viability kit as described previously, 16 with some modifications. Calcein-acetoxymethyl enters the cytosol where it is enzymatically cleaved to the green fluorescent calcein by esterases that are present in living cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from our research group have shown that cultured HLEC sheets can be stored in a closed container for 7 days at 23°C in bovine serum-containing storage medium [7,8]. Storage technology offers several advantages, including flexibility for both the patient and the surgeon in scheduling of surgery [9], sufficient time for sterility testing and other quality assessments [7], and time to transport cultured tissue e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With continuing improvement of RPE tissue engineering approaches, and with more than 20 million patients suffering from AMD worldwide, 4 an upcoming need for improved storage and transportation methods for cultured RPE is anticipated. A storage period of seven days is considered to be sufficient time to allow both phenotypical and microbiological assessment of the cultured transplants prior to surgery, 5 increased flexibility for scheduling surgeries, as well as transportation of transplants to eye clinics worldwide.…”
Section: Introductionmentioning
confidence: 99%